2013
DOI: 10.1523/jneurosci.0579-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Neurons Elaborate a Long-Range Projection with Shared Axonal and Dendritic Functions

Abstract: Information processing by neurons has been traditionally envisioned to occur in discrete neuronal compartments. Specifically, dendrites receive and integrate synaptic inputs while axons initiate and conduct spikes to distal neuronal targets. We report here in mice, using morphological reconstructions and electrophysiology, that the gonadotropin-releasing hormone (GnRH) neurons that control mammalian fertility do not conform to this stereotype and instead possess a single projection structure that functions sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
142
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 36 publications
14
142
0
1
Order By: Relevance
“…Recently, GnRH neuron cell filling coupled with electrophysiology demonstrated that GnRH neuron projections to the median eminence receive synaptic inputs along their complete length while also propagating action potentials (27). This "dendronic" morphology was compatible with prior evidence indicating that the GnRH fiber elements within and around the ME may be able to support episodic GnRH secretion (for review see ref.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, GnRH neuron cell filling coupled with electrophysiology demonstrated that GnRH neuron projections to the median eminence receive synaptic inputs along their complete length while also propagating action potentials (27). This "dendronic" morphology was compatible with prior evidence indicating that the GnRH fiber elements within and around the ME may be able to support episodic GnRH secretion (for review see ref.…”
Section: Discussionsupporting
confidence: 77%
“…The ARN kisspeptin, or KNDy cells, synthesize numerous neuropeptidergic and classic transmitters (20,23,35) and innervate only the distal processes of GnRH neurons in mice, either at the level of the dendron or their nerve terminals in the median eminence (36,37). We found that 2-Hz stimulation of ARN KNDy neurons was completely ineffective in modulating LH secretion.…”
Section: Discussionmentioning
confidence: 74%
“…These distal GnRH neuron projections, termed dendrons, are unusual in that they display both dendrite-and axon-like properties and are regulated directly by multiple neural inputs (35,36). We show here that ARN KISS neurons likely release kisspeptin for ∼1 min to generate an LH pulse.…”
Section: Discussionmentioning
confidence: 79%